2010
DOI: 10.1111/j.1743-4580.2010.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying: Developing a Human Rights Definition From the Perspective and Experiences of Targets

Abstract: Workplace bullying is a severe and pervasive problem. Targets of workplace bullying suffer devastating effects both personally and professionally. Bullying violates the human rights of the targets of bullying. Despite the seriousness of this problem, the definition of and measurement of incidents of workplace bullying has lacked proper focus. One indicator of this is the difference in incident rates between the operational and self-report methods of workplace bullying. Questions surround elements of many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
0
15
0
3
Order By: Relevance
“…Bunlardan birincisi öz bildirim ölçekleri olarak belirtilmiş olan psikolojik yıldırma kavramının ne olduğunun katılımcılara anlatıldığı ve kendilerinin bu tarz davranışlara maruz kalıp kalmadıklarının sorulduğu yöntemdir. Diğeri ise operasyonel yöntem olarak adlandırılmış olan, bir dizi davranış listesinin katılımcılara sunulduğu ve belirtilen her bir davranışa maruz kalıp kalmadıkları, şayet kaldılar ise ne sıklıkla ve ne süreyle maruz kaldıkları gibi soruları katılımcıların yanıtladığı yöntemdir (Carbo & Hughes, 2010). Operasyonel yöntem anket yöntemi ile yapılan saha çalışmalarında sıklıkla tercih edilirken, ölçümünde zaman içerisinde çeşitli versiyonları literatürde yer alsa da en çok atıf alan iki temel ölçeğe rastlanmaktadır.…”
Section: Psi̇koloji̇k Yildirma (Mobbing)unclassified
See 2 more Smart Citations
“…Bunlardan birincisi öz bildirim ölçekleri olarak belirtilmiş olan psikolojik yıldırma kavramının ne olduğunun katılımcılara anlatıldığı ve kendilerinin bu tarz davranışlara maruz kalıp kalmadıklarının sorulduğu yöntemdir. Diğeri ise operasyonel yöntem olarak adlandırılmış olan, bir dizi davranış listesinin katılımcılara sunulduğu ve belirtilen her bir davranışa maruz kalıp kalmadıkları, şayet kaldılar ise ne sıklıkla ve ne süreyle maruz kaldıkları gibi soruları katılımcıların yanıtladığı yöntemdir (Carbo & Hughes, 2010). Operasyonel yöntem anket yöntemi ile yapılan saha çalışmalarında sıklıkla tercih edilirken, ölçümünde zaman içerisinde çeşitli versiyonları literatürde yer alsa da en çok atıf alan iki temel ölçeğe rastlanmaktadır.…”
Section: Psi̇koloji̇k Yildirma (Mobbing)unclassified
“…Psikolojik yıldırmanın işyerlerinde karşılaşılan etik dışı bir davranış olmasının ötesinde mağdur çalışanlar için bir insan hakları ihlali meselesi olduğu unutulmamalıdır (Carbo & Hughes, 2010). Ancak diğer taraftan psikolojik yıldırma, bu tip eylemlere rastlanan örgütler açısından da oldukça yüksek maliyetler oluşturmaktadır.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…To develop such policies, organizations need acceptable definitions or at least descriptions of bullying, especially managerial bullying (Carbo and Hughes 2010;Greenwald 2010;Gradinger et al 2010;Yamada 2004). One study suggested that hierarchical status was not directly related to victimization (Aquino et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…in weight … fabricated with a cork center and wrapped in yarn or string … covered with leather strips sewn together. Although the terms bullying and harassment are widely used, the lack of precise definitions makes it difficult to distinguish between them [29] [30] [31]. There seems to be a need for a greater understanding of the similarities and differences among the many words used to describe or identify improper behavior [32] [33] [34].…”
Section: Introductionmentioning
confidence: 99%